Integrating Curriculum and Instruction In Islamic Religious Education : Insights from Robin Fogarty's Theory - Abu Nasir; Khozin Khozin; Abdul Haris (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research explores strategies to enhance the coherence between curriculum and instruction in Islamic Religious Education (IRE) by employing Robins Fogarty's theory of curriculum integration. Utilizing a qualitative approach with integrating a theoretical study as a research design. Specifically, the study highlights the utility of Fogarty’s tripartite integration model as a critical lens for developing a unified IRE curriculum. This model aims to synchronize disparate content areas, fostering a more integrated and holistic student understanding. For the data sources, the research examined the various theories linked with Forgaty’s theory, and the data analysis was qualitative, in which the research tried to explain and integrate the theory into IRE policy. The findings from the study emphasized the imperative for further applied research to develop integrated lesson plans, explore teachers’ experiences and professional development needs, and assess comprehensive learning outcomes. The research advocates for a collaborative approach between curriculum theorists and educators to refine and advance IRE policies. Such collaborative efforts ensure that IRE promotes intellectual advancement and contributes to students’ spiritual and personal growth, ultimately enriching their educational experience.